Simple church : returning to God's process for making disciples - Rainer, Thom S.; Geiger, Eric, 1975- (Nashville, Tennessee B&H Publishing Group, 2006)
"The simple revolution is here. From the iPod design to Google’s uncluttered homepage, simple ideas are changing the world. Multi-awarded #1 national bestseller Simple Church guides Christians back to the simple gospel-sharing methods of Jesus. No bells or whistles required. Based on case studies of 400 American churches, Thom Rainer and Eric Geiger prove the disciple-making process is often too complex. Simple churches thrive by taking four ideas to heart: Clarity. Movement. Alignment. Focus. Simple Church examines each idea, clearly showing why it is time to simplify." --
The simple revolution has begun -- The Simple (and not-so-simple) church in action -- Simple church : an extreme makeover -- Three simple stores -- Clarity : starting with a ministry blueprint -- Movement : removing congestion -- Alignment : maximizing the energy of everyone -- Focus : saying no to almost everything -- Becoming simple -- Research design methodology -- Frequently asked questions.
Includes bibliographical references (pages 253-256).
Keywords: Church growth; Evangelicalism